2011
DOI: 10.24302/drd.v1i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Aportes teórico-metodológicos sobre a dimensão espacial do desenvolvimento: uma contribuição

Abstract: Ao revisar as diferentes abordagens teóricas sobre desenvolvimento, apesar de não ser uma prática hegemônica, é digno de registro o fato que autores e obras da Economia e outras áreas ressaltam a dimensão espacial do desenvolvimento. Propõe-se contribuir no debate sobre desenvolvimento, sistematizando os aportes teórico-metodológicos centrados na dinâmica espacial, desde os clássicos até os contemporâneos. Os aportes teóricos, prefere-se classificá-los, como o conjunto de teorias clássicas da localização, as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Recognized as the founder of land use theory, von Thünen's work is the foundation for the development of the modern urban economy (Thisse, 2011). According to Dallabrida (2011) von Thünen focused studies on the analysis of distance, transport cost and market location, as explanatory variables of the pattern of agricultural land occupation. He demonstrated that market prices increased with increasing distance between production sites and the consumer market, an interpretation that led to the "Thünen rings", which are the circles around the city, each one corresponding to the area of production.…”
Section: Literature Review and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognized as the founder of land use theory, von Thünen's work is the foundation for the development of the modern urban economy (Thisse, 2011). According to Dallabrida (2011) von Thünen focused studies on the analysis of distance, transport cost and market location, as explanatory variables of the pattern of agricultural land occupation. He demonstrated that market prices increased with increasing distance between production sites and the consumer market, an interpretation that led to the "Thünen rings", which are the circles around the city, each one corresponding to the area of production.…”
Section: Literature Review and Methodsmentioning
confidence: 99%
“…natural. Dallabrida (2011), with a different theory, studies the nature of competition in space and the way in which companies choose their location in a strategic environment. In this model, the difference refers to the locational decision as a way to obtain a competitive advantage in relation to the competition.…”
Section: Literature Review and Methodsmentioning
confidence: 99%
“…Apontado como o fundador da teoria do uso do solo, o trabalho de Thünen (THISSE, 2011) é o alicerce para o desenvolvimento da moderna economia urbana. Segundo Dallabrida (2011), mesmo advertindo sobre a reduzida importância, na atualidade, dos custos de transporte aos custos totais da empresa, esse teórico focou seus estudos na análise da distância, no custo de transporte e na localização do mercado como variáveis explicativas do padrão de ocupação do solo agrícola. Demonstrou que os preços de mercado elevavam-se com o aumento da distância dos locais de produção em relação ao mercado de consumo, teoria esta chamada de "anéis de Thünen", que são as circunstâncias em torno da cidade, cada uma delas delimitando a área de cultivo de um produto.…”
Section: )unclassified
“…Com isso, os preços dos produtos sofreriam influência de acordo com sua distância em relação ao centro. Dallabrida (2011), com uma teoria diferente, estuda a natureza da competição no espaço e a maneira pela qual as empresas escolhem sua localização num ambiente estratégico. Neste modelo, a diferença refere-se à decisão locacional como forma de se ganhar vantagem competitiva em relação à concorrência.…”
Section: )unclassified
“…Em suma, pode-se afirmar que desenvolvimento é algo que combina crescimento com distribuição de renda. Muitos são os estudos recentes que analisam o processo de desenvolvimento regional e territorial (DALLABRIDA et al, 2011;DALLABRIDA, 2012;DALLABRIDA, 2020a;DALLABRIDA, 2012b;SILVA (2017); SOARES; RABÊLO, 2011;VILLELA, et al, (2017); ZAZYKI; MOURA (2019). Ora, nas economias regionais, geralmente este movimento está ligado à um segmento produtivo que oferece as condições de geração de renda para se realizar um adequado desenvolvimento.…”
Section: Introductionunclassified